On Designing Contracts to Guarantee Enforceability: Theory and Evidence from East-West Trade - Kogut, Bruce (Journal of International Business Studies, 1986)
This article suggests how the literature on East-West trade and the choice of contracts can be integrated into recent work on the theory of the multinational corporation and contract enforceability. By using the properties of foreign direct investment as a benchmark, it explains why one type of contract tends to prevail over another. The explanation rests on the premise that because of the prohibition on FDI, contracts are used which most closely replicate the benefits of intra-firm trade, while providing managerial and risk-shifting services to the eastern partner.